the CORRELATION BETWEEN SEA SURFACE TEMPERATURE AND CONVECTIVE CLOUDS IN AMBON ISLANDS - Pasaribu, Puput Mustika; Tubalawony, Simon; Masrikat, Julius Anthon Nicolas (Pusat Penelitian dan Pengembangan BMKG, 2025)
Sea surface temperature (SST) plays a key role in modulating tropical convection, yet its influence on the vertical structure of convective clouds in island-based, anti-monsoonal regions remains poorly quantified. This study examines the relationship between SST variability and convective cloud characteristics over the coastal waters of Ambon Island during 2023. Daily SST data were obtained from ERA5 reanalysis, while convective parameters Convective Condensation Level (CCL) and Equilibrium Level (EL) were derived from twice-daily radiosonde observations. Owing to non-normal distributions and serial autocorrelation, Spearman rank correlation was applied with effective sample size (ESS) correction and bootstrap confidence intervals. Results show that SST exhibits a pronounced seasonal cycle primarily governed by monsoonal forcing. SST displays a moderate positive correlation with CCL (ρ = 0.532-0.580) and a consistently strong correlation with EL across all stations (ρ = 0.770-0.778; p_adj < 0.001), indicating a stronger SST control on convective depth than on cloud-base height. Although large-scale climate modes (ENSO, IOD, and MJO) contribute to short-term variability, seasonal monsoonal forcing remains the dominant modulator of SST-convection coupling. These findings represent robust statistical associations and highlight the importance of ocean-atmosphere coupling in regulating convective cloud structure in tropical maritime island environments.